Egocentric social network correlates of physical activity - Sonja Mötteli; Simone Dohle (Elsevier, 2020)
Background: The social environment might play an important role in explaining people's physical activity (PA) behavior. However, little is known regarding whether personal networks differ between physically active and physically inactive people. This study aimed to examine the relationship between personal network characteristics and adults' physical (in)activity. Methods: An egocentric social network study was conducted in a random sample in Switzerland (n = 529, mean age of 53 years, 54% females). Individual and personal network measures were compared between regular exercisers and non-exercisers. The extent of these factors' association with PA levels was also examined. Results: Non-exercisers (n = 183) had 70% non-exercising individuals in their personal networks, indicating homogeneity, whereas regular exercisers (n = 346) had 57% regularly exercising individuals in their networks, meaning more heterogeneous personal networks. Additionally, having more regular exercisers in personal networks was associated with higher PA levels, over and above individual factors. Respondents with an entirely active personal network reported, on average, 1 day of PA more per week than respondents who had a completely inactive personal network. Other personal network characteristics, such as network size or gender composition, were not associated with PA. Conclusion: Non-exercisers seem to be clustered in inactive networks that provide fewer opportunities and resources, as well as less social support, for PA. To effectively promote PA, both individuals and personal networks need to be addressed, particularly the networks of inactive people (e.g., by promoting group activities).